Multi-agent, non-equilibrium, and network models of labour economics and financial contagion - Del Rio Chanona, RM (2021)
The financial crisis of 2009 showed that the economy is not in equilibrium. That is, the economy is in a state where agents have incentives to modify their chosen actions. The recent COVID-19 pandemic has shown that the economy changes rapidly and that reaching an equilibrium can take years, if one is reached at all. However, assuming equilibrium has long formed the basis of many economic models. Although a non-equilibrium approach may seem better suited for answering economic policy questions during times of rapid change, previously, the lack of data and computing power made it difficult to build these type of models. Today, these factors are less constraining.